The rigid S-type cable-suspended parallel robot design, modelling and analysis. Issue 9 (9th December 2014) - Filipovic, M.; Djuric, A.; Kevac, Lj.
SUMMARY: This paper presents design, modelling and analysis of the selected Rigid ropes S-type Cable-suspended Parallel Robot (RSCPR). The characteristic of this system is its geometric construction which defines the kinematic model through the Jacobian matrix. The relationship between external and internal forces is defined by the Lagrange principle of virtual work. The Jacobian matrix is directly involved in the application of the Lagrange principle of virtual work and generation of the dynamic model of the RSCPR system. Selected examples of the CPR system types are analysed and the comparison of their results is presented. The software package named ORIGI has been developed for the RSCPR model verification.